The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1071/rd9960969
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin transfer across the isolated placenta is influenced by maternal and fetal albumin concentrations

Abstract: The aim of this study was to evaluate the influence of different maternal and fetal albumin concentrations on the transplacental transfer and the placental tissue accumulation of digoxin. Digoxin passage across the isolated lobules of 15 human placentae was calculated from repeated fetal and maternal perfusate samples, and placental tissue digoxin concentrations were measured at the end of the experiments. Metildigoxin (Lanitop) was added to the maternal medium at a concentration of 5.70 +/- 0.73 ng mL-1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Because only the unbound drug fraction can cross the placenta, the balance between maternal and fetal concentrations of drug‐binding proteins is of particular importance. For example, the placental transfer of digoxin in the perfused cotyledons has been observed to be dependent on the albumin concentrations in both circuits . Also, as discussed later on, the difference in the pH value between the maternal and fetal blood may be another relevant factor influencing the transfer of weakly basic drugs, which should be accounted for in these experiments.…”
Section: Models For Placental Drug Transfermentioning
confidence: 91%
See 1 more Smart Citation
“…Because only the unbound drug fraction can cross the placenta, the balance between maternal and fetal concentrations of drug‐binding proteins is of particular importance. For example, the placental transfer of digoxin in the perfused cotyledons has been observed to be dependent on the albumin concentrations in both circuits . Also, as discussed later on, the difference in the pH value between the maternal and fetal blood may be another relevant factor influencing the transfer of weakly basic drugs, which should be accounted for in these experiments.…”
Section: Models For Placental Drug Transfermentioning
confidence: 91%
“…For example, the placental transfer of digoxin in the perfused cotyledons has been observed to be dependent on the albumin concentrations in both circuits. 89,90 Also, as discussed later on, the difference in the pH value between the maternal and fetal blood may be another relevant factor influencing the transfer of weakly basic drugs, which should be accounted for in these experiments. Despite these challenges, a recent study of 26 drugs showed that the prediction of ex vivo placenta perfusion matches the observed in vivo data well.…”
Section: Ex Vivo Cotyledon Perfusion Experimentsmentioning
confidence: 98%